2020
DOI: 10.1093/mnras/staa3061
|View full text |Cite
|
Sign up to set email alerts
|

G133.50+9.01: a likely cloud–cloud collision complex triggering the formation of filaments, cores, and a stellar cluster

Abstract: We present compelling observational evidence of G133.50+9.01 being a bona fide cloud-cloud collision candidate with signatures of induced filament, core, and cluster formation. The CO molecular line observations reveal that the G133.50+9.01 complex is made of two colliding molecular clouds with systemic velocities, $\rm -16.9\, km\, s^{-1}$ and $\rm -14.1\, km\, s^{-1}$. The intersection of the clouds is characterised by broad bridging features characteristic of collision. The morphology of the shocked layer a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…While some proposed bridging features are remarkably similar to those in the Haworth et al (2015a) simulations (Torii et al 2011), others are much less clear-cut (e.g. Issac et al 2020, although we note that those authors present a significant quantity of other evidence in favour of a cloud collision).…”
supporting
confidence: 62%
“…While some proposed bridging features are remarkably similar to those in the Haworth et al (2015a) simulations (Torii et al 2011), others are much less clear-cut (e.g. Issac et al 2020, although we note that those authors present a significant quantity of other evidence in favour of a cloud collision).…”
supporting
confidence: 62%
“…The first cluster to be identified as a possible collision object was Westerland 2, which harbors two associated clouds with a velocity difference of 20 km s −1 (Furukawa et al 2009;Ohama et al 2010) approximately. Other recent observations by Fukui et al (2014), Torii et al (2015), Baug et al (2016), Dewangan & Ojha (2017), Dewangan et al (2018Dewangan et al ( , 2019, Issac et al (2020) have also detected CCCs in the high-mass star forming regions.…”
Section: Introductionmentioning
confidence: 71%
“…Simulations of Haworth et al (2015a,b) suggested that a broad intermediate-velocity feature that bridges between two colliding clouds will appear in a PV diagram. The bridge feature probes the turbulent motion of the gas enhanced by the collision and often appears at the spots of collisions (Issac et al 2020;Gong et al 2017). The increased velocity dispersion along the U-shape, especially at the bottom where the compressed layer formed (see the top right panel of Fig.…”
Section: Bridgementioning
confidence: 96%
“…First, we examined whether G323.18a and G323.18b are gravitationally bound as one structure. The virial mass was determined using the expression (Pillai et al 2011;Issac et al 2020)…”
Section: Signatures Of Cccsmentioning
confidence: 99%
See 1 more Smart Citation